Análise da fidedignidade dos dados estatísticos hospitalares disponíveis na Secretaria de Estado da Saúde de São Paulo em 1974 Accuracy analysis of the available hospital statistical data at the S. Paulo State Health Department - Maria Lúcia Lebrão (Universidade de São Paulo, 1978)
Foi analisada a fidedignidade dos dados estatísticos hospitalares recebidos pela Coordenadoria de Assistência Hospitalar da Secretaria de Estado da Saúde de São Paulo. Mediante uma amostra sistemática por conglomerado em etapa única, com base nas saídas de pacientes relacionados nos Boletins 101 - "Movimento de Pacientes Saídos" - foram visitados 31 hospitais de assistência hospitalar geral e examinados 7.021 prontuários de pacientes saídos durante um mês. A perda de prontuários foi em média de 19,64%. Houve concordância de dados quanto à idade, procedência, data de admissão e tipo de saída, respectivamente de 97,08%, 96,93%, 98,47% e 99,82%. Relativamente à data de saída, a discordância média foi de 7,43%, com valores de até 65,64% e 82,51% de erro, sendo analisados alguns fatores responsáveis por esses resultados. Quanto aos diagnósticos, verificou-se que há um aumento da relação de diagnósticos por paciente, na medida em que se examinam o Boletim 101 e os prontuários, e que alguns diagnósticos tais como anemias, desnutrição e verminoses apareceram inúmeras vezes nos prontuários sem a devida transcrição no Boletim 101. Em 17,51% dos casos, os diagnósticos registrados nos Boletins não concordaram com os diagnósticos dos prontuários, havendo 458 saídas (6,52%) onde o único diagnóstico registrado era um estado mórbido mal definido, tendo sido possível reduzir, mediante análise dos prontuários, esse número para 174 casos (2,48%). The objective of this paper was to analyze the accuracy of hospital statistical data collected by means of the "Model 101 Report" of the S. Paulo State Health Department, Brazil. The "Model 101 Report" summarizes the data on discharged patient records and is sent monthly to the Health Department by each hospital in the State of S. Paulo. A one stage systematic cluster sampling of these data was performed. Only general care hospitals entered the sample. Thirty one hospitals with 7,021 medical records of discharged patients in a given month were reviewed. The mean loss percentage of medical records at the sample hospitals was 19.64%, reaching as high as 40.00% or more at some of them. The identifying information and personal data relating to each patient were correct in 97.08% of the cases (age data) and 96.93% of the cases (area of residence). The administrative information was correct in 98.47% of the cases (date of admission) and 99.82% of the cases (discharge status). Only the items of death or routine live discharge were checked. The date of discharge was wrong in 7.43% of the cases, as a mean, reaching as high as 65.64% and 82.51% in two of the hospitals. Some factors potentially responsible for these results were analyzed. There was an increase in the actual number of diagnoses relative to each patient after the medical records were checked. Also diagnoses such as: anemia, malnutrition and parasitosis were present many times in the medical records, without being transcribed to the discharge summary and therefore to the "Model 101 Report''. In 1,404 cases (17.51%) the diagnoses on the "Model 101 Report" were erroneous. There were 458 (6.52%) discharges with an ill-defined condition as the unique diagnosis. It was possible to reduce this figure to 174 cases (2.48%) by checking the medical records. Only 69.21% of the forms were considered entirely correct, i.e., with all the items correctly and completely transcribed.